The correlation of serum/plasma IGF-1 concentrations with obstructive sleep apnea hypopnea syndrome: A meta-analysis and meta-regression - He, Jie; Li, Xiaoyan; Yu, Mi (Frontiers in Endocrinology, 2022)
Background: A common disease known as obstructive sleep apnea hypopnea syndrome (OSAHS) has serious cardiovascular and metabolic effects. The level of Insulin-Like Growth Factor 1 (IGF-1) is reduced in OSAHS patients. However, whether blood IGF-1 levels are lowered in OSAHS patients is still a matter of debate. As a result, the link of serum/plasma IGF-1 levels with OSAHS was investigated in this meta-analysis. Methods: Wan Fang, EMBASE, Web of Science, CNKI, VIP, PubMed, and other databases were searched for material published in any language before April 2, 2022, were searched in. Two researchers analyzed the studies for a quality check based on the Newcastle-Ottawa Scale. The acquired data were analyzed using STATA 11.0 and R 3.6.1. The effect size was estimated and calculated using the standard mean difference (SMD) and the correlation coefficient, and the combined analysis was carried out using either a random effect model or a fixed-effect model. Results: 34 studies met the recruiting criteria. Findings of this report revealed that the concentration of plasma/serum IGF-1 in OSAHS patients was greatly reduced as compared to that in healthy subjects. A subgroup analysis was carried out according to OSAHS severity, ethnicity, age, body mass index (BMI), specimen testing method, and study design type. The outcomes suggested that almost all the subgroups of OSAHS patients had reduced serum IGF-1. Disease severity and difference in ethnicity were identified to be possible influencing factors of serum IGF-1 level in patients with OSAHS, in meta-regression analysis and no other factors were found to alter the plasma/serum IGF-1 concentration. Moreover, plasma/serum IGF-1 concentrations were negatively correlated with an apnea-Hypopnea index (AHI) and oxygen-desaturation index (ODI), while they were positively associated with minimum oxygen saturation. Conclusion: Serum/serum IGF-1 concentration in OSAHS patients was greatly reduced in comparison with the control group, which was negatively linked with AHI, negatively correlated with ODI, and positively correlated with minimum Oxygen saturation.